Avaliação de fatores que afetam a qualidade de farinha de vísceras na indústria de subprodutos avícola - Fernandes, Eder de Sousa (2016)
In order to characterize the possible variations in the chemical composition of the viscera meal was carried out this work to study the possible variables that can cause variations and affect the final quality of poultry by products focusing on their use in the feed industry broilers. For this experiment was chosen a large commercial poultry abattoir processing viscera immediately after slaughter of birds in a processing plant poultry meal, unit is located in central Goiás state. The samples were collected and analyzed weekly for a period of twelve months between June 2014 and June 2015. in order to characterize the possible variations in the chemical composition of the viscera flour were studied the effect of temperature, pressure, humidity, weight and processing time and to assess the flours obtained the parameters were qualitative tests (acidity index, peroxide index and Eber test), the proximal evaluation (ether extract, crude protein, moisture, calcium and phosphorus), and this grading tests were performed, color texture and odor. For such an assessment adopted the statistical program R using the statistical method of Pearson correlations.